Perspektif Remaja terhadap Pembelajaran Al-Qur’an Studi Kasus Minat Remaja Belajar Membaca Al-Qur’an - Azmi, Nahdliyah Islamiyah; Ashoumi, Hilyah (JoEMS (Journal of Education and Management Studies), 2024)
The study seeks to understand adolescents' views on the benefits of learning to read the Qur'an, the reasons for their disinterest, and ways to encourage it. The method is qualitative. Data is collected by observation, interviews, and documentation. Miles and Huberman theory is used to reduce, present, and derive conclusions from data. Testing data validity by triangulation, case analysis, and member check. Adolescents are less motivated to read the Qur'an due to (1) lack of knowledge of its benefits (2) exhaustion after a day of school (3) and peer pressure. Many adolescents don't grasp the necessity of memorizing the Qur'an, hence they have limited motivation to learn it. (2) a friendship setting that discourages teens from learning the Qur'an (3) poor family role models, such as parents and other family members who don't practice religion, which reduces adolescents' enthusiasm in memorizing the Qur'an. (4) TPQ's boring learning methods bore teens. Teenager-friendly Qur'an-reading programs are insufficient.